Earphone Use Patterns and Hearing Loss Risk Affecting Quality of Life - Lina Marliana; Sena Pongtuluran; Fransiskus Harf Poluan (The Indonesian Institute of Science and Technology Research, 2026)
In today's modern life, most people are constantly exposed to noise every day, potentially disrupting their hearing function. One such factor is the use of hearing devices, namely earphones. Approximately 1.1 billion young adults and adolescents are at risk of experiencing hearing loss in their lifetime. If someone is at risk of hearing loss, it can undoubtedly impact their quality of life. Participants in this study were students at the Christian University of Indonesia in 2019, 2020, and 2021. The purpose of this study was to determine whether risky earphone use patterns are associated with quality of life. Data for this study were collected using a cross-sectional observational analytical methodology with a consecutive sampling technique. The study sample was assessed with a questionnaire created using Google Forms. The questionnaire, which is divided into two parts: the Earphone Use Pattern Questionnaire (PPE) and the Hearing Handicap Inventory for Adults (HHIA), to determine the patient's quality of life, was then analyzed using the Chi-Square and Spearman tests. Of the 225 respondents, there were 62.2% risky earphone usage patterns and 37.8% non-risky earphone users. According to the HHIA score findings, 74.2% of people had no disabilities, 9.8% had mild to moderate disabilities, and 16.0% had severe disabilities, with p = 0.015 (p <0.05) obtained through the use of the Chi-Square statistical test. There is a relationship between earphone usage patterns and the risk of hearing loss, which affects the quality of life of students of the Faculty of Medicine, Universitas Kristen Indonesia, Class of 2019, 2020, and 2021.